2018
DOI: 10.1080/13645706.2018.1464029
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous vein ablation with a new cyanoacrylate glue device: a systematic review on 1000 cases

Abstract: NBCA injection with the Variclose device seems to be a feasible, effective and safe treatment in GSV incompetence. Long-term follow-up studies and randomized controlled trials are needed to achieve high-quality evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
0
23
3
3
Order By: Relevance
“…1 Cyanoacrylate glue also appears to be a safe method of treatment, with a low rate of complications reported in clinical studies. 6 Reported complications are typically mild and managed either conservatively or on an outpatient basis and include pain, thrombophlebitis, cellulitis, skin hyperpigmentation and deep vein thrombosis. 7,8 However, clinical studies currently published do not have large patient cohorts, leading to the reasonable concern that they are underpowered to detect rare complications.…”
Section: Discussionmentioning
confidence: 99%
“…1 Cyanoacrylate glue also appears to be a safe method of treatment, with a low rate of complications reported in clinical studies. 6 Reported complications are typically mild and managed either conservatively or on an outpatient basis and include pain, thrombophlebitis, cellulitis, skin hyperpigmentation and deep vein thrombosis. 7,8 However, clinical studies currently published do not have large patient cohorts, leading to the reasonable concern that they are underpowered to detect rare complications.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,30 Bissacco et al reviewed 1,000 NBCA cases in seven studies (two prospective, four retrospective) and found 96.8% of veins occluded at 12 months. 38 Two studies reported NBCA occlusion beyond the 2-year interval, and these were 94.1% at 30 months and 94.7% at 36 months, respectively. 20,28 Time to complete occlusion was shorter for NBCA than any of the endothermal modalities because veins are instantly occluded by approximation of their intima, while thermal ablation is dependent on vein wall destruction and subsequent fibrosis-a biological process which takes longer.…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis would have been ideal but as highlighted in a recent article, the scarcity and heterogeneity of RCTs made this difficult. 38 As most patients were not sedated, double blinding was impossible. Outcome assessors were often the same ones recruiting, carrying out the treatments and/or following-up patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, occlusion rates remain quite similar to those seen in a recent systematic review including non-RCT studies (six month occlusion rate 97.3% in the systematic review vs. 98.1% in the RCT; one year occlusion rate 97.0% in the systematic review vs. 94.7% in this RCT). 2 Conversely, there were more post-operative complications in the RCT than in the systematic review (ecchymosis 5.4% vs. 0.8% and phlebitis 6.5% vs. 1.9%, respectively). Despite differences in results among studies, this RCT confirms encouraging outcomes for NBCA for uncomplicated (C2 C4) patients with GSV incompetence.…”
mentioning
confidence: 81%